2001
DOI: 10.1007/s11627-001-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration through somatic embryogenesis and rapd analysis of regenerated plants in Tylophora indica (Burm. F. Merrill.)

Abstract: A procedure for the regeneration of complete plantlets of Tylophora indica from cultured leaf callus via somatic embryogenesis is described. Callus induction from leaf explants was on Murashige and Skoog (MS) medium with different concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D; 0.0±3 mg l 21 ; 0.0±13.56 mM) and kinetin (Kn; 0.01 mg l 21 ; 0.05 mM). The best response for callus induction was obtained on MS medium containing 2 mg l 21 (9.04 mM) 2,4-D and 0.01 mg l 21 (0.05 mM) Kn. After two subcultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 25 publications
(29 reference statements)
4
37
0
1
Order By: Relevance
“…A number of molecular markers can be used to assess the genetic fidelity of in vitro derived plants. However random amplified polymorphic DNA (RAPD) is efficient and cheapest among these markers (Jayanthi and Mandal 2001). In the present investigation, culture conditions were established for improved maturation and germination of somatic embryos and plantlet development in C. borivilianum from embryogenic suspension culture.…”
Section: Introductionmentioning
confidence: 99%
“…A number of molecular markers can be used to assess the genetic fidelity of in vitro derived plants. However random amplified polymorphic DNA (RAPD) is efficient and cheapest among these markers (Jayanthi and Mandal 2001). In the present investigation, culture conditions were established for improved maturation and germination of somatic embryos and plantlet development in C. borivilianum from embryogenic suspension culture.…”
Section: Introductionmentioning
confidence: 99%
“…Over-exploitation and a lack of organized cultivation has led to a rapid decline in the wild population of T. indica (Jayanthi and Mandal 2001). Micropropagation of T. indica by axillary shoot induction and adventitious shoot production (Sharma and Chandel 1992) and callusmediated somatic embryogenesis from leaf (Jayanthi and Mandal 2001) and stem (Rao et al 1970;Rao and Narayanaswamy 1972) explants have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Jayanthi and Mandal ( 2001 ) obtained somatic embryos from leaf-derived callus. For callus induction MS medium supplemented with different concentrations of 2, 4-D (2.26-13.56 μM) and 0.05 μM Kn was used.…”
Section: Somatic Embryogenesismentioning
confidence: 99%